The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.
Publisher: University of California Press

Par les mains pour les yeux : les représentations de l'identité sourde au sein de performances artistiques de la scène montréalaise - Paradis Vigneault, Marie-Claude (Université Laval, 2012)
Ce mémoire s’appuie sur une recherche ethnographique réalisée principalement au sein de la communauté sourde de Montréal et tente de déceler les représentations de l’identité sourde au sein de performances artistiques de la scène montréalaise. Le but de cette recherche est d’inscrire la culture sourde dans les réflexions sociales et scientifiques portant sur l’expression identitaire de minorités culturelles par les arts. Afin de démontrer les liens à la fois théoriques et pratiques entre l’identité sourde et celles de minorités socio- politiques, telles que les Noirs, les gays, les femmes ou les Queers, cette étude s’appuie sur les concepts de performativité (Judith Butler), de performance (Clifford Geertz et Victor Turner) et de représentations (Stuart Hall et Serge Moscovici). Y seront également démontrées les relations entre ces notions, le vécu des sujets, leur agency et leur expression artistique.